Avaliação do perfil de citocinas pró e anti-inflamatórias em pacientes com Covid-19 grave - Coutinho, Lucyana Leoncio Carrijo (2023)
COVID-19 is an acute respiratory infectious disease with multisystem inflammatory potential. The dysregulation in innate and acquired immune responses promotes a cytokine storm, responsible for inducing a hyperinflammation process that is one of the main causes of death, especially in elderly individuals or those with comorbidities. This cross-sectional observational study evaluated pro- and anti-inflammatory cytokines in unvaccinated patients who tested positive for SARS-CoV-2 infection and were admitted to the ICU of a hospital in Fortaleza from 2020 to 2021. Serum samples were collected on admission hospital of 78 patients. The kit used was customized with 20 cytokines (GM-CSF, MCP-1, TNF-α, IFN-α and IFN-γ, IL-1β, IL-10, IL-12p70, IL-13, IL-17A, IL -18, IL-2, IL-21, IL-22, IL-23, IL-27, IL-4, IL-5, IL-6 and IL-9) called the Human ProcartaPlex Multiplex Immunoassay (Thermo Fisher Scientific, MA , USA). The concentration of the concentrations of each biomarker was performed on the MAGPIX® System based on Luminex xMAP technology. Clinical and laboratory data, as well as sociodemographic data, were analyzed to seek association with the clinical outcomes deaths (n = 40) and recovered (n = 38). Most of the group of deaths was made up of men (70%). The median age for the total was 59 years (IQR=22-97), and the group of deaths had a median of 69.5 years (IQR=22-97). Among the comorbidities, systemic arterial hypertension (SAH) was the most frequent (30.7%). In the laboratory data analyzed, there was a statistical difference between the results in the platelet count, with a smaller number in the group of deaths (p=0.0063). Of the 20 quantified cytokines, only four were statistically significant. IL-18 and IL-22 showed differences for deaths, with p=0.009 and p=0.473, respectively. While GM-CSF (granulocyte and macrophage colony stimulating factor) and IL-23 had a difference in the discharge group, with p=0.0187 and p=0.313, respectively. In all analyses, statistical significance was considered at p < 0.05. Early investigation of cytokines together with clinical characteristics and other markers serve as predictors of good or poor prognosis for COVID-19. In this way, they help in the types of therapeutic targets to be used for each group, so that fatal outcomes can be reduced or avoided.